Anti-Muslim Propaganda on Twitter and the Role for the Far-Right - Elizabeth Poole (Medya ve Din Araştırmaları Dergisi, 2018)
Following Donald Trump’s retweeting of Britain First’s anti-Muslim videos, this article shows how the far-right have previously used Twitter as a platform for anti-Muslim propaganda but also to boost the profile and political success of Donald Trump and his political allies. After the Brussels terrorist attack of 2016, some mainstream media outlets reported on a racist hashtag #StopIslam that had been ‘hijacked’ by anti-racists to counter the negative publicity being peddled about Muslims in the aftermath of the attack. This inspired us to seek funding from the British Academy and the Leverhulme Trust to investigate the dynamics of this campaign. What we found was surprising. We expected to find a preponderance of European far right voices in the debate but we were wrong!